PHYSICO-CHEMICAL CHARACTERISTICS AND HEAVY METAL CONTENT OF THOUBAL RIVER MANIPUR - CHANU, NINGTHOUJAM KAMALA; SINGH, KH. RAJMANI (Journal of the Inland Fisheries Society of India, 2021)
Thoubal river flows through the boundary of Manipur State and one of the major tributaries of the Imphal river that originates from the hill ranges of Ukhrul. Physico-chemical quality of water was assessed every month from January to December 2012. Nutrient status was analysed for alternate months, whereas heavy metals were estimated of every third month i.e. monsoon, post monsoon and lean season, pre-monsoon season.